The Role of Cadastral Surveyor in Land Measurement in Complete Systematic Land Registration in Semarang City - Fairus Augustina Rachmawati; Ana Silviana (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
In guaranteeing legal certainty to holders of Land Rights (HAT), what is called land registration is carried out as a form of implementation carried out by the Government. Land registration itself is regulated in Government Regulation Number 24 of 1997 concerning Land Registration. At the land registration stage, a physical and juridical data collection process is required wherein the physical data collection is carried out by the measuring officer or a Licensed Cadastral Surveyor. So that in this study aims to find out more about the role of the Licensed Cadastral Surveyor in the process of measuring land parcels in the Complete Systematic Land Registration program in Semarang City and the regulations governing the role of the Licensed Cadastral Surveyor in terms of measuring land parcels. This study used qualitative normative methods with data collection techniques using library research and observations made in Sampangan and Bendan Duwur Villages, Semarang City. The results of the study show that the role of the Licensed Cadastral Surveyor in the Complete Systematic Land Registration conducted in the City of Semarang is very important in measuring land parcels and collecting data by always paying attention to the Delimitation Contradictory Principle. Regulations regarding Licensed Surveyors are guided by the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the Republic of Indonesia Land Agency Number 22 of 2016 and Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 9 of 2021 concerning Licensed Surveyors.